The Ka-band high power klystron amplifier design program of INFN. (September 2021) - Behtouei, M.; Spataro, B.; Di Paolo, F.; Leggieri, A.
Abstract: In the framework of the Compact Light XLS project, a short ultra-high gradient linearizer working on the third harmonic of the main linac frequency is requested. Increasing gradients and reducing dimensions are requirements for XLS and all next generation linear accelerators. Actually, ultra-compact normal conducting accelerating structures, operating in the Ka-band are required to achieve ultra-high gradients for research, industrial and medical applications, with electric field ranging from 100 to 150 MV/m. To fulfill these strong requirements, the R&D of a proper Ka-band klystron with high RF power output and a high efficiency is mandatory. This contribution reports the design of a possible klystron amplifier tube operating on the T M 010 mode at 36 GHz, the third harmonic of the 12 GHz linac frequency, with an efficiency of 42% and a 20 MW RF power output. This contribution discusses also the high-power DC gun, the beam focusing channel and the RF beam dynamics.